TENTANG TOTO SUDARTO BACHTIAR DAN PEMBELAJARAN APRESIASI PUISI “RUMAH” - Nugraha, Dipa (ATAVISME, 2024)
Toto Sudarto Bachtiar is one of Indonesia's well-known poets. With different themes, Toto's name is sometimes compared with the names or works of major Indonesian poets such as Chairil Anwar or Sitor Situmorang by several literary critics. This article discusses the life, role, and influence of Toto so that it can emphasize the important position and urgency of Toto's poems in poetry appreciation learning in Indonesia. Apart from that, this article uses close reading in discussing the poetry work entitled "Rumah" so it can become an example on how poetry appreciation is done.